The GmCYCLOPS paralogs regulate soybean nodulation and exhibit signatures during domestication - Yuanting Lei; Zhi Liu; Qiang Chen; Xintong Wu; Ming Li; Fulong Liu; Yuzhen Liu; Zhitong Yin; Siyuan Zhao; Pengshuo Shen; Yuan Zhao; Sobhi F. Lamlom; et al. (Plant Science, 2026)

Three-dimensional spherical ordered mesoporous Al-MCM-48 solid acid catalysts for the rapid conversion of biomass-derived GVL to butene - Haibiao Yu; Yudong Li; Yuanting Du; Ruixi Yang; Weijun Shan; Yuejiao Wang; Ruan Chi; Ying Xiong (Fuel, 2026)

Robust prediction of CO2 absorption in blended amines via structure-concentration integration: A machine learning approach for imbalanced and data-scarce systems - Binmin Li; Tengxian Qin; Zehua Xu; Zhi Yang; Guiyang Ye; Jiaoying Huang; Yuanting Qiao; Xuelan Zeng; Song He; Yawen Zheng; Junyao Wang (Journal of Environmental Chemical Engineering, 2026)

Supranutritional dietary vitamin D3 promoted the skin wound healing in turbot, Scophthalmus maximus L. - Zhichu Chen; Yuanyuan Fang; Yuanting Li; Xinhua Chen; Mingzhu Pan; María Ángeles Esteban; Kangsen Mai; Yanjiao Zhang; Dong Huang (Aquaculture, 2026)

Effect of oxygen vacancies induced by doping rare earth metal elements (La³⁺, Ce³⁺/⁴⁺, Nd³⁺) in NaTaO3 thin films on photocatalytic and antibacterial properties - Cuicui Wang; Shuxian Dong; Ruixue Yin; Anqi Cai; Haoyu Li; Zhizun Yue; Hongxia Ren; Chuanli Zhang; Hairong Yin; Yuanting Wu (Journal of Environmental Chemical Engineering, 2026)

High Carbohydrate Feeding Exacerbates Oxidative Stress and Intestinal Dysfunction in Red Seabream (Pagrus major) after Skin Wounding - Zhichu Chen; Yuanting Li; Yuanyuan Fang; Dong Huang; M. Ángeles Esteban; Yanjiao Zhang (Marine Biotechnology, 2026)

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Polyphenol-mediated hierarchical porous hydrogel evaporators for accelerated water transport and reduced evaporation enthalpy - Xueqian Zhang; Hongtao Li; Bo Liang; Zikun Zou; Zhen Yang; Shaohui Xiong; Lei Yang; Xu Wang; Yang Chen; Yuanting Xu; Yiwen Li (Science Bulletin, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Comparative analysis of nutritional and flavor compound alterations in Cordyceps militaris juice fermented by single or mixed Lactobacillus strains - Zeyang Li; Zhongxu Sun; Qingping Wu; Huiying Huang; Yuanting Tang; Jingwei Nan; Zhenjun Zhu; Yu Ding (Food Research International, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Adsorption of radioiodine by metal sulfides and relevant derivatives - Wei Zheng; Xiaoxuan Chen; Hao Xu; Duxia Li; Yuanting Zhang; Wanliang Yang; Meisong Xu; Dehong Gong; Mengkui Tian (Journal of Cleaner Production, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Differences in spatial pattern of expressway passenger and freight flows based on OTC data: A case study of Guangdong, China - Yuanjun Li; Yuanting Li; Qitao Wu; Zhuo Chen; Yunhao Yang (Applied Geography, 2025)

Hollow Fe2O3-NiFe2O4 hetero-nanoframes coupled with N-doped graphene for boosted electrochemical water oxidation through optimizing intermediate bonding - Yuanting Li; Ya Zhang; Ruidong Shi; Xiaoxin Xu; Xue Wang; Gongbing Zhou (Chemical Engineering Journal, 2025)

Robust mussel-inspired LBL carbon nanotube-based superhydrophobic polyurethane sponge for efficient oil–water separation utilizing photothermal effect - Guoyan Yang; Yuxin Zhang; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Haitao Yang; Yidan Luo; Zhen Hong; Mingshan Xue (Fuel, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Transcriptome analysis of the genes and regulators involving in vitamin E biosynthesis in Elaeagnus mollis diels - Shuhui Du; Yuanting Guo; Qianqian Li; Xiaoyan Hu; Yang Tian; Baochang Cheng; Shengji Wang; Zhiling Wang; Ruifen Ren; Zhaoshan Wang (Plant Molecular Biology, 2024)

Gut microbiota mediates ambient PM2.5 exposure-induced abnormal glucose metabolism via short-chain fatty acids - Wenpu Shao; Bin Pan; Zhouzhou Li; Renzhen Peng; Wenhui Yang; Yuanting Xie; Dongyang Han; Xinyi Fang; Jingyu Li; Yaning Zhu; Zhuohui Zhao; Haidong Kan; et al. (Journal of Hazardous Materials, 2024)

Promotion of manganese on Fe-based catalyst for the production of carbon nanotubes (CNTs) from plastics - Su He; Chunchun Li; Hongman Sun; Christopher M.A. Parlett; Yuanting Qiao; Youhe Wang; Yikai Xu; Ningbo Gao; Chunfei Wu (Chemical Engineering Journal, 2024)

Facile construction of multifunctional 3D smart MOF-based polyurethane sponges with photocatalytic ability for efficient separation of oil-in-water emulsions and co-existing organic pollutant - Qidong Zha; Yuankun Yao; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Yidan Luo; Mingshan Xue (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Estimation of expressway carbon emissions and simulation of policies based on OTC data: A case study of Guangdong, China - Yuanjun Li; Qitao Wu; Yuanting Li; Yunhao Yang; Hailing Wu; Yong Sun (Urban Climate, 2024)

An ultra-high-temperature cavity receiver with a simple flat absorber for safe and efficient solar-thermal conversion - Jikang Wang; Yuanting Zhang; Yu Qiu; Qing Li (Journal of Cleaner Production, 2024)

Preparation of high-performance asymmetric supercapacitors based on NiCo2S4 nanospheres and CuO-MOF nanosheets on carbon fibers - Baopeng Liu; Jun Zhang; Jiawei Xu; Yanjie Pan; Yanshan Huang; Sheng Han; Yuanting Li (Fuel, 2024)

Detection and analysis of potential landslides based on SBAS-InSAR technology in alpine canyon region - Yimin Li; Xianjie Feng; Yuanting Li; Wenxue Jiang; Wenxuan Yu (Environmental Science and Pollution Research, 2023)

Optical-thermal-stress analysis of a multiscale solar receiver for ultra-high-temperature concentrating solar power - Yuanting Zhang; Qing Li; Yu Qiu (Journal of Cleaner Production, 2023)

Cholinergic anti-inflammatory pathway mediates diesel exhaust PM2.5-induced pulmonary and systemic inflammation - Yuanting Xie; Shimin Tao; Bin Pan; Wenhui Yang; Wenpu Shao; Xinyi Fang; Dongyang Han; Jingyu Li; Yubin Zhang; Renjie Chen; Weihua Li; Yanyi Xu; et al. (Journal of Hazardous Materials, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

A harsh environment resistant robust Co(OH)2@stearic acid nanocellulose-based membrane for oil-water separation and wastewater purification - Zuozhu Yin; Min Li; Zihao Li; Yuanting Deng; Mingshan Xue; Yuhua Chen; Junfei Ou; Sheng Lei; Yidan Luo; Chan Xie (Journal of Environmental Management, 2023)

Toxicity effects of disinfection byproduct chloroacetic acid to Microcystis aeruginosa: Cytotoxicity and mechanisms - Jing Ye; Jiawei Ni; Fuxiang Tian; Xiyan Ji; Meifang Hou; Yuanting Li; Lei Yang; Runxiang Wang; Wenwu Xu; Liang Meng (Journal of Environmental Sciences, 2023)

Adaption of tobacco rattle virus to its solanaceous hosts is related to the codon usage bias of the hosts and that of the viral 16 K gene - Qi Lin; Yuanting Zheng; Yueyan Yin; Yi Chen; Miaomiao Li; Hongying Zheng; Jianping Chen; Fei Yan; Yuwen Lu; Shengchun Xu (European Journal of Plant Pathology, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

The monthly variation tendency of microcystin-LR levels in the Huangpu River (China) by applications of ELISA and HPLC - Sijia Hua; Jiawen Chen; Liang Wu; Xinyue Yu; Jing Ye; Yuanting Li; Yongqiang Zhu; Fuxiang Tian (Environmental Science and Pollution Research, 2022)

Activation of the bitter taste sensor TRPM5 prevents high salt-induced cardiovascular dysfunction - Hao Wu; Yuanting Cui; Chengkang He; Peng Gao; Qiang Li; Hexuan Zhang; Yanli Jiang; Yingru Hu; Xiao Wei; Zongshi Lu; Tianyi Ma; Daoyan Liu; et al. (Science China Life Sciences, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Recombinant expression of different mutant K-ras gene in pancreatic cancer Bxpc-3 cells and its effects on chemotherapy sensitivity - TengFei Shao; YuanTing Zheng; Bei Zhao; Tao Li; KeGuang Cheng; WeiMin Cai (Science China Life Sciences, 2014)